Development of jute, cotton and sheep wool blended yarn using cotton spinning system - Hossain, MT; Ershaduzzaman, M; Jubayer, MMU; Molla, JB; Majumder, MKH (Bangladesh Journal of Livestock Research, 2020)
A large number of farmers are rearing sheep in Bangladesh. Enormous quantity of local sheep wool are wasted due to lack of processing and proper applications. As the consciousness is growing for the use of natural fibre products, this wool can play a significant role. If proper processing technology can be employed in this sector, the natural fibre will be a good resource for us and will meet today’s necessity in all respects of life. Wool is normally collected from sheep by shearing in our country. A total of about 2.5 thousand metric tons of raw wool can be collected from local sheep every year. Therefore, the present experiment was undertaken to know the physico-mechanical properties of blended yarn. Wool and jute were treated with chemicals, washed, dried and opened to form spin able fibre. After that, jute, cotton and wool fibres were turned to blended yarn through cotton processing system. In results, it was observed that 30% wool, 30% jute and 40% cotton fibre 12s blended yarn used for blended yarn production. Therefore, Wool, jute and cotton blended yarn may be a new horizon for developing diversified products. Bangladesh J. of Livestock Res. 21-25: 173-177, 2018